Study on the needs and availability of health care services for elders in the divisional director of health services area of Akkaraipattu - Riyaz, A.M.M (My University, 2000)
The elderly population was 5.65 per cent, the sex ratio (men : female) was 81.8 per cent in the study area 15 per cent were over 76 years.Among the elders, 69.1 per cent (N=220) of females, and 20 per cent (N=180) of males were widowed and 11.3 per cent (N=400) of elders were living alone.48.6 per cent of elders never attended school, and 82.8 per cent of elders had either no income at all or income of less than 1,000 rupees per month.The impairment of activities of daily living (ADL) and instrumental activities of daily living (IADL) were 8.5 per cent and 29.5 per cent respectively; while both were significantly high in elders over 76 years.The elders were mainly suffering from the chronic diseases like arthritis, high blood pressure and chronic cough, and higher number of chronic respiratory ailments in elderly females requires further investigation. The problem of vision,impairment of hearing,dementia and depression among elders were found to be more common when compared to other studies done in sri lanka.Therefore, it is recommended that necessary steps to be taken to provide these specialised medical care facilities in this district, and provide spectacles and hearing aids on free of charge to poor elders.